Family circumstances and relationships as a factor of children crime behavior - Marković, Mirjana M; Lakićević, Miloš (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2020)
Statistics show that crime rates are rising globally. Not a single period of the development of human society was spared from the pathological phenomena and deviant behavior, nor even the modern era, where an explosion of various forms of deviant behavior can actually be noticed. What are the conditions and causes that have led to such global trends?In this paper, family circumstances and relationships will be analyzed as a crime factor. We will see what the universal and unchanged characteristics of the family are, how it affects the socialization, cultivation and individualization of children. In one systematic way, we will try to respond to the universal issues of family influence on its members. What are the interactive relationships between family members? How the functional and dysfunctional families affect their members? If and how can a family create a favorable climate for deviant behavior and how to avoid the multiplication of pathological phenomena in dysfunctional families? All these are questions that we will try to give an answer to, although this answer is unlikely to be one-dimensional, since the family is a complex social group, with a complex mechanism of action.
Keywords: family; crime; socialization; children; deviant behavior